y=-5(-1+-1y)-17

Simple and best practice solution for y=-5(-1+-1y)-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-5(-1+-1y)-17 equation:



y=-5(-1+-1y)-17
We move all terms to the left:
y-(-5(-1+-1y)-17)=0
We add all the numbers together, and all the variables
y-(-5(-1y)-17)=0
We calculate terms in parentheses: -(-5(-1y)-17), so:
-5(-1y)-17
We multiply parentheses
5y-17
Back to the equation:
-(5y-17)
We get rid of parentheses
y-5y+17=0
We add all the numbers together, and all the variables
-4y+17=0
We move all terms containing y to the left, all other terms to the right
-4y=-17
y=-17/-4
y=4+1/4

See similar equations:

| 9x-23+12x-56=180 | | 2x2-2x-112=0 | | 10x+55=180 | | 68-m=9(m+9) | | 7+y=-29 | | x-1/3+2x-4/5=4 | | x+35=149 | | 55x=70x+30 | | 12(4a)=12(4a) | | 72=(x)(x-1)(x+9) | | 2x/3+5x/4=23/24 | | 3t+64=t+84 | | d+79=2d-7 | | 12v+67=31v-47 | | (4x+1)^2-2(4x+1)=15 | | (4x+1)^2-2(4x+1)-15=0 | | 2/5x+6=5/7 | | 2x/7-x/3=4 | | 2(x-3)-3(x-1)=5-(x+1) | | 21/x=x/84 | | 54/x=x/6 | | x^2+8x+5=15 | | 144=12r+36 | | X+2=5x-6 | | 40=(w)(w+6) | | 3x−5=9 | | W*w+6=40 | | 3(x+4)^2=48 | | 9(x+8)=180 | | 15x2-x-2=0 | | 1/10-x=50 | | x+19.34=23.8972 |

Equations solver categories